A6 EFFECTS OF ELUXADOLINE TREATMENT ON ABDOMINAL AND BOWEL SYMPTOMS IN PATIENTS WITH IRRITABLE BOWEL SYNDROME WITH DIARRHEA REPORTING INADEQUATE SYMPTOM CONTROL WITH LOPERAMIDE: AGGREGATED RESULTS FROM PHASE 3 AND 4 CLINICAL TRIALS. (26th February 2020) - Brenner, D M; Sayuk, G; Saeed, M; Janiszewski, P; Liu, L W
Abstract: Background: The heterogeneous nature of irritable bowel syndrome with diarrhea (IBS-D) presents a complex challenge in the management of a wide range of symptoms. Despite the need for more effective treatments that provide global IBS-D symptom relief, many therapies currently available in Canada only treat individual IBS-D symptoms. Eluxadoline (ELX) is a mixed µ- and κ-opioid receptor agonist and δ-opioid receptor antagonist approved by Health Canada for the treatment of IBS-D in adults. Aims: To analyze the efficacy of ELX for managing a constellation of IBS-D symptoms among patients (pts) self-reporting inadequate responses to loperamide (LOP) from Phase 3 and 4 trials of ELX. Methods: Adults with IBS-D were randomized to placebo (PBO) or ELX (75 or 100 mg) twice daily (BID) for 26 or 52 weeks in two Phase 3 trials (NCT01553591 and NCT01553747); the data from a subset reporting inadequate IBS-D symptom control with prior LOP use were pooled and prospectively analyzed. In the Phase 4 trial (RELIEF: NCT02959983), IBS-D pts with self-reported inadequate symptom control with LOP over the previous 12 months were randomized to PBO or ELX 100 mg BID for 12 weeks. In all trials, pts recorded their daily IBS-D symptoms including worst abdominal pain (0–10 scale), stool consistency (Bristol Stool Form Scale score 1–7), and daily urgency episodes. Results for ELX 100 mg vs. PBO were evaluated after 12 weeks of treatment, which included the generation of radar plots to visualize multiple efficacy endpoints. Results: Of pts enrolled in the Phase 3 trials with prior LOP use, inadequate control of IBS-D symptoms was reported in 58.9% (n=166) and 58.8% (n=174) of pts in the PBO and ELX groups, respectively; in the Phase 4 trial, 174 and 172 pts were treated with PBO and ELX, respectively. ELX-treated pts had a greater proportion of responders compared to PBO-treated pts for all outcomes, including a significant increase in the proportion of pts achieving both ≥50% and ≥75% urgency-free days in the Phase 3 trials (Figure ). Analysis of the global symptoms of pts enrolled in the Phase 4 trial further supported these results. Across Phase 3 and 4 trials, adverse events occurred in similar proportions regardless of treatment, with the most common being nausea. Conclusions: In pts with inadequate responses to LOP, a greater proportion of ELX-treated pts were responders compared to PBO-treated pts in all Phase 3 and 4 trials for the respective primary composite endpoints, abdominal pain, stool consistency, and urgency after 12 weeks of treatment. These results validate the effectiveness of ELX in alleviating IBS-D symptoms in this population. Funding Agencies: Writing assistance by Complete HealthVizion, funded by Allergan plc